SLANG AND SOCIAL NETWORKS: THREAT OR DEVELOPMENT TO CHANGES IN YOUTH LANGUAGE - Umurzakova, Kommuna (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
This paper examines the impact of slang and social networks on the evolution of youth language, evaluating whether these influences represent a threat to linguistic integrity or a catalyst for linguistic innovation. Slang, often emerging from informal social interactions, and the communicative dynamics of social networks significantly shape the linguistic practices of young people. Through analyzing examples from digital communication, cultural studies, and linguistic theory, this study investigates how these phenomena contribute to the diversification and adaptation of language. While some argue that the prevalence of slang and online communication erodes linguistic standards, others suggest they enhance linguistic creativity and foster cultural identity. The paper concludes by addressing the dualistic nature of these influences and proposing areas for further research.